Children’s Neural Sensitivity to Prosodic Features of Natural Speech and Its Significance to Speech Development in Cochlear Implanted Children - Chen, Yuebo; Luo, Qinqin; Liang, Maojin; Gao, Leyan; Yang, Jingwen; Feng, Ruiyan; Liu, Jiahao; Qiu, Guoxin; Li, Yi; Zheng, Yiqing; Lu, Shuo (Frontiers in Neuroscience, 2022)
Catchy utterances, such as proverbs, verses, and nursery rhymes (i.e., “No pain, no gain” in English), contain strong-prosodic features and are child-friendly in repeating and memorizing; yet the way that prosodic features being encoded by neural activity and their influence on speech development in children are still largely unknown. Using functional near-infrared spectroscopy, this paper investigated the cortical responses to the perception of natural speech sentences with strong/weak-prosodic features and evaluated the speech communication ability in 21 prelingually deaf children with cochlear implantation (CI) and 25 normal hearing children. A comprehensive evaluation of speech communication ability was conducted on all the participants to explore the potential correlations between neural activities and children’s speech development. The strong-prosodic information evoked right-lateralized cortical responses across a broad brain network in normal hearing children, and facilitated early integration of linguistic information, highlighting children’s neural sensitivity to natural strong-prosodic sentences. In contrast, CI children showed significantly weaker cortical activation and characteristic deficits in speech perception with strong-prosodic features, suggesting hearing loss in early age of life causes significantly impaired sensitivity to prosodic features of sentences. Importantly, the level of neural sensitivity to strong-prosodic sentences was significantly related to the speech behaviors of all children participants. These findings demonstrate the significance of speech prosodic features in children’s speech development.